Barriers and facilitators to patient education from nursing perspectives in West bank hospitals: a Cross-sectional study - Mohammad Hayek; Ibrahim Ghoul; Abdullah Abdullah; Nizar Said; Aidah Alkaissi; Eman Alshawish; Fatima Mohammad Hirzallah; Amer Asia; Murad Jkhlab; Nansy Daas; Baraa Salah; Joud Abutair; et al. (BMC Nursing)
Abstract Background Patient education is fundamental to patient-centered care but faces significant implementation challenges. Nurses, ideally positioned to lead education, encounter barriers like time constraints, inadequate environments, and discontinuity across shifts, leading to inconsistent delivery. Understanding these barriers and facilitators from nurses’ perspectives is crucial for improving practice, especially in resource-constrained settings like Palestine. Methodology A cross-sectional study was conducted with 150 nurses (mean age 32.1 ± 11.4 years; 58% female; 62% governmental hospitals; 58.7% open units) across diverse Palestinian hospitals. A validated 20-item questionnaire (Cronbach’s α = 0.89 overall) assessed 10 barriers and 10 facilitators using a 5-point Likert scale. Data analysis employed descriptive statistics, non-parametric tests (Mann-Whitney U, Kruskal-Wallis H), and ordinal logistic regression via SPSS v25. Results Top barriers were time limitations (37.3%; mean = 3.52 ± 1.06), unsuitable environment (33.3%; 3.46 ± 1.16), and discontinuity across shifts (32.0%). Key facilitators included prioritizing education evaluation (48.0% agreed; 3.63 ± 1.10), using educational technology (44.0% agreed; 3.67 ± 1.07), and dedicated nurse-educators (46.0% agreed). Significant predictors of higher barriers were older age (p < 0.001), governmental hospitals (p = 0.005), and lower education (Diploma/Bachelor vs. PhD, p < 0.05). Facilitators were more recognized by older nurses (p < 0.001), those in urban areas (B = 1.034, p = 0.016), and governmental staff (p = 0.015). Conclusions Systemic barriers (time, environment, staffing) and actionable facilitators (technology, evaluation protocols, specialized roles) critically impact patient education in Palestine. Interventions must prioritize resource allocation, protected education time, Arabic-language tools, and leveraging experienced nurses. Policy reforms addressing nurse-patient ratios and institutional support are essential to enhance education quality and patient outcomes. Clinical trial registration This research did not involve a clinical trial; no clinical trial registration is applicable.